2017
DOI: 10.1038/s41598-017-16923-z
|View full text |Cite
|
Sign up to set email alerts
|

Highly-Sensitive Thin Film THz Detector Based on Edge Metal-Semiconductor-Metal Junction

Abstract: Terahertz (THz) detectors have been extensively studied for various applications such as security, wireless communication, and medical imaging. In case of metal-insulator-metal (MIM) tunnel junction THz detector, a small junction area is desirable because the detector response time can be shortened by reducing it. An edge metal-semiconductor-metal (EMSM) junction has been developed with a small junction area controlled precisely by the thicknesses of metal and semiconductor films. The voltage response of the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…A similar behavior was noticed in an edge metal-semiconductor-metal (EMSM) lateral junction based on Ni/Au/SiC/Ni (see, e.g. [45],). The voltage response of this heterostructure increases under THz radiation due to the enhanced nonlinearity of I-V characteristics at definite applied biases.…”
Section: Elliptically Polarized Radiationsupporting
confidence: 71%
“…A similar behavior was noticed in an edge metal-semiconductor-metal (EMSM) lateral junction based on Ni/Au/SiC/Ni (see, e.g. [45],). The voltage response of this heterostructure increases under THz radiation due to the enhanced nonlinearity of I-V characteristics at definite applied biases.…”
Section: Elliptically Polarized Radiationsupporting
confidence: 71%
“…The nonlinear behaviour of the I−V curve is important for device application like electromagnetic radiation detectors. Jeon et al [37] have shown that a sensitive THz detector based on metal-semiconductor-metal junction with non-linear I−V characteristics will have sensitivity dependent on the ratio I″/I′, where I″ and I′ are the second and first derivatives of I with respect to V, respectively. The rectified voltage output of THz detectors is proportional to the ratio I″/I′.…”
Section: Electrical Conductivity Measurementsmentioning
confidence: 99%
“…Since the residual resist can be up to 1 to 2nm thick [6], it is also prohibitive to use graphene in surface-sensitive plasmonic applications [7] or to fabricate reliable tunneling barriers with other graphene or metal electrodes [8]. The tunneling is a fast transport mechanism that could be used for high-speed graphene rectifiers, as demonstrated for metal-insulator-metal diodes [9], with the advantage of atomic thickness, smaller capacitance, and faster response times. However, the graphene-oxidemetal interface must be sharp on the nanometer length scale to fully exploit its potential for electro-optical applications [10].…”
Section: Introductionmentioning
confidence: 99%